Testing Linear Hypothesis on National Account Data - Weale, Martin (The Review of Economics and Statistics, 1985)
Stock adjustment models of money demand have employed either the nominal or real adjustment process, but they have not been tested statistically due to their nonnested- ness. This paper formulates a general stock adjustment model which includes both nominal and real adjustment processes as its nested subsets. Each process is then tested against the general specification. The paper also examines the homogeneity of money demand with respect to price level and income in the general model.